"n Literêr-kritiese ondersoek na die belang van die jubilee in die Bybel - Volschenk, G. J. (HTS teologiese studies, 2002)
A literary-critical study of the significance of the jubilee in the BibleThe aim of this article is that the literary critical study of the land in the Old Testament and the New Testament provides a holistic, coherent hermeneutic framework for the interpretation of the Biblical jubilee. Martens (1981) describes land as an integral part of the four part plan of God. God’s plan is a coherent and organizing principle within the exegesis of Old Testament texts. Martens doesn’t describe the multidimentional nature of land in the Old Testament and New Testament. The triangular model of Wright (1983) describes the interrelationship of God, land, people, and house in detail. Wright’s model accentuates the multidimentional nature of land in the Old interpreting the Biblical jubilee.